Implementation of a Personalized Weight Training Protocol and Influence of Sleep Duration - Giechaskiel, Barouch (Journal of Sports Research, 2018)
Weight (resistance) training can increase strength and muscle mass. A personalized training protocol (i.e., with optimum frequency and number of sets) was followed for 4 months by a 40-year old male with 20 years of weight training experience. The body was split in three parts and was trained every 5-6 days. The strength increase was between 7% (back) and 17% (legs), while the free-fat mass increase was 0.4 kg (0.5%), which was lost after the 4-month period. It was shown that reduced sleep duration for one night did not affect the strength performance. However, with 2 days of reduced sleep, there were indications of worse performance. The results confirm the importance of personalized weight training programs and good sleep habits for strength improvements.